PENGARUH MASSAGE KAKI TERHADAP PENURUNAN INSOMNIA PADA LANSIA DI PANTI WERDHA HANA TANGERANG SELATAN - Royani; Diana Rahayu; Tirta Yenti (STIKes IMC Bintaro, 2020)
Insomnia is the inability to sleep although there is a desire to do so. The elderly are at risk of experiencing a disruption of normal sleep patterns caused by several factors such as changes in social patterns, retired, life partner or a close friend, the use of drugs, disease in natural elderly, mood disorders, ansietas, the confidence to sleep, death, and negative feelings is an indicator of the onset insomnia. Foot Massage is a therapy of non pharmacological, is merely using human hands and can be done without using the physical assistance of another person, in doing a massage on the muscles of the feet then it can improve circulation blood, smoothen the flow of blood to the jantuung. The goal in this research is to know the influence of masase feet against a decrease of insomnia in the elderly pasa werdha hana South Tangerang. Type of this research is Quantitative Research with experimental quasy pre and post test whit non equivalents and control group, in which the quasi experimental research . The population of the research was the entire elderly in anti werdha hana Tangerang to the southern numbering 80 elderly. Sampling techniques using Simple Random Sampling. Methods of data analysisusing a Test with a test of Wilcoxon Signed Rank Test. The results of the analysis before and after done Group intervention is showed a p value 0.05, in the control group was 0.01 or p < 0.05 then can be concluded there is a significant difference between the influence of Therapeutic Massage of the feet against the decrease of Insomnia in the Elderly There Werdha Hana City South Tangerang after performed intervention.